Age-, season- and gender-specific reference intervals of serum 25-hydroxyvitamin D3 for healthy children (0 ~ 18 years old) in Nanning area of China - Dong-yi Zhou; Shang-mou Wei; Chun-ling Zhu; Yu-hong Wei; Xiao-mei Wang; Li-ling Yi; Si-tao Yang; Qi-liu Peng (Journal of Physiological Sciences)
Abstract Establishing specific reference intervals (RIs) of serum 25-hydroxyvitamin D3 [25(OH)D] for children is essential for improving the accuracy of diagnosis and prognosis monitoring of diseases such as rickets and growth retardation. The study including 6,627 healthy children was conducted to establish specific RIs of 25(OH)D for children in Nanning area of China. The results showed that there were statistically significant differences among age, season, and gender of serum 25(OH)D levels, and the age-specific RIs of serum 25(OH)D were 20.3 ~ 53.6 ng/mL for 0 ~  ≤ 1 year and 18.9 ~ 49.6 ng/mL for 2 ~  ≤ 3 years. The age-, season-specific RIs of serum 25(OH)D for 4 ~  ≤ 6 years in spring–summer and autumn–winter were 15.8 ~ 42.6 ng/mL and 15.2 ~ 37.7 ng/mL, respectively. The age-, gender-specific RIs of serum 25(OH)D for 7 ~  ≤ 18 years for males and females were 12.1 ~ 36.1 ng/mL and 10.8 ~ 35.3 ng/mL, respectively. This study successfully established the RIs of serum 25(OH)D, which may help to improve disease diagnosis and monitoring for children in the Nanning area of China.